A cultural history of Japanese Buddhism - Deal, William E. (Wiley-blackwell guides to Buddhism, 2015)
"Offers a vivid, nuanced, and chronological account of Buddhistreligion in Japan -- from its emergence in the sixth centuryright through to the present day"--